KETERKAITAN VARIABEL BRAND AWARENESS, BRAND IMAGE, BRAND QUALITY DAN BRAND VALUE TERHADAP BRAND LOYALTY - Verinita, Verinita (BISMA: Jurnal Bisnis dan Manajemen, 2019)
This study aims to analyze the effect of brand awareness, brand image, brand quality, and brand value on brand loyalty of the domestic tourists visiting Air Manis Beach, Padang City, West Sumatra Province. This research is a quantitative survey employing a purposive sampling technique with the sample consisted of 105 domestic tourists. Data were analyzed using multiple linear regression run by SPSS version 16. Results showed that brand awareness has a positive but not significant effect on brand loyalty. This indicated that the reputation and good characteristics of Air Manis Beach do not significantly influence loyalty. The brand image had a significant and positive effect on brand loyalty, which means that a good image can increase loyalty. Brand quality had a significant and positive effect on brand loyalty, which means that accommodation, safety, cleanliness, good experience, and interesting attractions can increase loyalty. Brand value had a negative and not significant effect on brand loyalty, which means that the high price of the tourism destination cannot increase tourist loyalty. Domestic tourists wish to visit a tourism destination that provides interesting and unique experiences and attractions offering at a reasonable price.